Knowledge Base Of Lecturers In Teaching Reading Comprehension At Teachers Training Institutes: A Case Study - Leong , Lai Mei; Surin, Basil Jude (Penerbit Universiti Sains Malaysia, 2007)
The focus of this study was the knowledge bases of teacher training institute lecturers with regard to teach reading comprehension to Post-Graduate Teaching Diploma Course (KPLI) students who took the English Studies subject. The study involved four lecturers and it looked into the types of knowledge bases that they draw upon. Data was obtained via semi-structured interviews. From the data, six knowledge bases, which were subsumed in a typology of pedagogical content knowledge, emerged. In this report, the knowledge bases of these lecturers in teaching reading comprehension to their students are described.